2019
DOI: 10.1016/j.resuscitation.2019.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Closed chest compressions reduce survival in an animal model of haemorrhage-induced traumatic cardiac arrest

Abstract: Closed chest compressions (CCC) are recommended for medical cardiac arrest, but there is little evidence to support their inclusion for traumatic cardiac arrest (TCA). This laboratory study evaluated CCC following haemorrhage-induced TCA and whether resuscitation with blood improved survival compared to saline.The study was conducted with the authority of UK Animals (Scientific Procedures) Act 1986 (received institutional ethical approval and a Home Office Licence) using 39 terminally anesthetised, instrumente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…Yet it has been reported that the earlier the transfusion is started, the lower the transfusion requirements and the lower the mortality [29,30]. In the cases where cardiac arrest is secondary to exsanguination, only cardiopulmonary resuscitation with PRBC transfusion allowed for a sustainable return of spontaneous circulation [31]. However, a massive transfusion of PRBCs has been shown to worsen metabolic disorders such as hypocalcaemia and thus increase mortality by worsening coagulopathy disorders [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Yet it has been reported that the earlier the transfusion is started, the lower the transfusion requirements and the lower the mortality [29,30]. In the cases where cardiac arrest is secondary to exsanguination, only cardiopulmonary resuscitation with PRBC transfusion allowed for a sustainable return of spontaneous circulation [31]. However, a massive transfusion of PRBCs has been shown to worsen metabolic disorders such as hypocalcaemia and thus increase mortality by worsening coagulopathy disorders [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…While there is very limited specific evidence to guide management of CPA due to exsanguination, it is reasonable to manage these cases similarly to patients with hemorrhagic shock not in CPA. A recent porcine study in which exsanguination cardiac arrest was induced by peripheral arterial hemorrhage, intra-arrest resuscitation with whole blood compared to 0.9% NaCl was significantly more effective in achieving ROSC (22). In people, a combination of fresh frozen plasma (FFP) and packed red blood cells (PRBC) at a ratio of 1:1 or 1:2 has been suggested, with the addition of cryoprecipitate and platelet concentrate as needed to prevent dilution of fibrinogen and platelets (23).…”
Section: Types Of Resuscitation Fluidsmentioning
confidence: 95%
“…Bei einem Kreislaufstillstand aufgrund einer Hypovolämie, Herzbeuteltamponade oder einem Spannungspneumothorax ist es unwahrscheinlich, dass Thoraxkompressionen so effektiv sind wie bei einem normovolämischem Kreislaufstillstand und sie können das verbleibende spontane Herzzeitvolumen verringern [ 46 48 ]. Thoraxkompressionen haben daher eine niedrigere Priorität als die Behandlung der reversiblen Ursachen.…”
Section: Evidenz Die In Die Leitlinien Einfließtunclassified